Pelayanan Publik dalam Pengurusan Izin Mendirikan Bangunan (IMB) Melalui Sistem Informasi Perizinan Satu Pintu Kabupaten Kediri (SIMPATIK) - Sheilla Yufe Faradila; Saputra Agus Santoso (Program Studi Ilmu Administrasi Negara Fakultas Ilmu Sosial dan Politik Universitas Sebela, 2022)
This study discusses public services for the management of building permits through the Kediri Regency One-Stop Integrated Licensing Information System (SIMPATIK). In the management of IMB in Kediri Regency, there were community complaints because the process of obtaining permits to build complex buildings and took time. It should not take long when taking care of the building permit process. The Kediri Regency Investment and One-Stop Integrated Service Office launched an electronic-based service called SIMPATIK (Kediri Regency Integrated Licensing Information System). The theory used is the theory from Ratminto and Atik Septi (2005) which has 11 basic dimensions of licensing services. The method used in this study is a qualitative method, which is to observe aspects of criteria related to public services through building permits. Informant selection technique uses purposive sampling. Primary data collection is carried out by interviews and secondary data is obtained from documents related to the object of study. Data collection techniques by conducting observations, interviews, and documentation. Data analysis according to Miles and Huberman 1992. The results showed that the 11 basic dimensions of IMB licensing services through SIMPATIK in the Kediri Regency DPMPTSP produced good public services but there were still problems that arose, namely coming from the community.